2021
DOI: 10.3389/fphar.2021.789075
|View full text |Cite
|
Sign up to set email alerts
|

Kratom Use in the US: Both a Regional Phenomenon and a White Middle-Class Phenomenon? Evidence From NSDUH 2019 and an Online Convenience Sample

Abstract: Kratom products available in the United States are becoming increasingly diverse both in terms of content and in terms of how they are marketed. Prior survey research indicates that kratom has been primarily used in the US to self-treat anxiety, depression, pain, fatigue, and substance use disorder (SUD) symptoms. Kratom is also well-known for its use as a short- or long-term full opioid agonist substitute. Therefore, use may be greater in regions particularly impacted by addiction to prescription opioids. Use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 58 publications
(73 reference statements)
0
11
0
2
Order By: Relevance
“…Eine aktuelle Analyse von Kommentaren aus sozialen Median von Kratomkonsumenten aus den USA zwischen 06/2019 und 06/2020 zeigte, dass die Mehrheit Kratom zur Behandlung von Opioidentzugssymptomatik, geringer auch zur Substitution von Opioiden nutzten 22 . Im Rahmen einer Auswertung von zwei Befragungen waren weiße Hautfarbe, Zugehörigkeit zur Mittelklasse, und vorstädtischer Wohnort mit Kratomkonsum assoziiert 23 . Eine Online-Befragung von US-amerikanischen Erwachsenen, die angaben, in den letzten sechs Monaten Alkohol, Opioide und/oder Stimulantien konsumiert zu haben, ergab als stärkste Prädiktoren für den Konsum von Kratom den Konsum anderer psychotroper Substanzen wie Cannabidiol, Psychedelika und verschreibungspflichtiger Opiode sowie früheren Gebrauch von Opioidagonisten 24 .…”
Section: Materials Und Methodenunclassified
See 1 more Smart Citation
“…Eine aktuelle Analyse von Kommentaren aus sozialen Median von Kratomkonsumenten aus den USA zwischen 06/2019 und 06/2020 zeigte, dass die Mehrheit Kratom zur Behandlung von Opioidentzugssymptomatik, geringer auch zur Substitution von Opioiden nutzten 22 . Im Rahmen einer Auswertung von zwei Befragungen waren weiße Hautfarbe, Zugehörigkeit zur Mittelklasse, und vorstädtischer Wohnort mit Kratomkonsum assoziiert 23 . Eine Online-Befragung von US-amerikanischen Erwachsenen, die angaben, in den letzten sechs Monaten Alkohol, Opioide und/oder Stimulantien konsumiert zu haben, ergab als stärkste Prädiktoren für den Konsum von Kratom den Konsum anderer psychotroper Substanzen wie Cannabidiol, Psychedelika und verschreibungspflichtiger Opiode sowie früheren Gebrauch von Opioidagonisten 24 .…”
Section: Materials Und Methodenunclassified
“…Eine weitere Auswertung von zwei Befragungen zeigte eine Lebenszeitprävalenz bzgl. Kra tomkonsum von 1,1 % und eine Prävalenz von 6,7 %, Kratom im letz ten Jahr konsumiert zu haben [23]. Zufällig durchgeführte Kontrol len motorisierter Verkehrsteilnehmer in Thailand zwischen 12/2005 und 03/2006 zeigten eine Prävalenz von Kratom von 0,9 % (vs. 5,5 % Alkohol, 2,0 % Antihistaminika, 1,8 % Amphetamine und 1,1 % Can nabis) in Urinuntersuchungen [31].…”
Section: Konsumprävalenzunclassified
“…Data from the 2020 National Survey on Drug Use and Health (NSDUH) indicate that among people who used stimulant drugs (i.e., cocaine, methamphetamine, MDMA, and prescription stimulants) in the past year, past-year kratom use was overrepresented relative to the US population (20.8% vs. 6.6%, F(1, 50) = 10.62, p = 0.002) [58]. Indeed, data from both surveys and case reports document lifetime, past-year, or past 30-day use of kratom and contemporaneous use of alcohol, opioids, and/ or stimulants, but no causal or otherwise explanatory associations can be made with respect to polydrug use broadly or drug substitution or nonmedical management of SUD symptoms specifically [59][60][61][62][63]. These findings have not been detected among US adolescents (there, nicotine and cannabis displayed the strongest relationship) [64].…”
Section: Drug Substitution and Nonmedical "Self-treatment" In The Con...mentioning
confidence: 99%
“…Kratom users in this sample were also more likely to have ever participated in MOUD treatment. Complete survey data from this crowdsourced study (see [62] included 2615 responses with 11.1% reporting lifetime kratom use. From this sample, 129 kratom-using respondents were re-recruited for follow-up [5 •].…”
Section: Drug Substitution and Nonmedical "Self-treatment" In The Con...mentioning
confidence: 99%
“… 13 Reported estimated prevalence of past-year kratom use in the U.S. ranges from 0.7% to 4.1%. 10 , 14 - 16 People using this herb tend to be males, 13 , 15 , 17 - 19 middle-aged, 13 , 15 , 17 , 19 employed, 13 , 17 - 19 have an household income of $35 000 or more, 13 , 17 , 19 and possess at least some college education. 17 Prior research has revealed geographic variations in kratom exposure rates reported to U.S. poison control centers and in kratom use patterns.…”
Section: Introductionmentioning
confidence: 99%